Investigation of electrospun poly (ε-caprolactone) fiber mats loaded with Calophyllum inophyllum essential oil for wound dressing applications: Morphology, drug release and in vitro evaluation - Ustundag, Cem Resat; Piskin, Mehmet Burcin (TAYLOR & FRANCIS LTD, 2023)
In this study, Calophyllum inophyllum (CIO) loaded Poly (e-caprolactone) (PCL) electrospun fibre mats were produced for potential wound healing applications. Physiochemical evaluation and in vitro characterisation of produced mats were evaluated. Average fibre diameters of the mats were determined as 0.9 +/- 0.3 mu m, 1.2 +/- 0.2 mu m, 1.3 +/- 0.2 mu m, and 1.5 +/- 0.1 mu m for PCL, PCL/CIO -2.5, PCL/CIO-5 and PCL/CIO-7.5, respectively. The contact angle values of the fibre mats were decreased up to 30 +/- 5 (degrees) compared to oil-free PCL fibre mat, indicating improved surface wettability. The incorporation of CIO into fibre mats led to a two-fold increase in the anti-bacterial activity, as compared to the fibre mats composed of PCL. In vitro cytotoxicity evaluation indicated that all the fibre mats had increased cell viability compared to the control. The findings suggest that CIO-loaded PCL electrospun fibre mats have potential for use in tissue engineering applications.
Keywords: electrospinning; wound dressing; essential oil; poly(epsilon-caprolactone); anti-bacterial activity; TISSUE; FABRICATION; CHITOSAN; Materials Science